A case study on selecting process of third party logistics in Triways Logistics Sdn. Bhd / Mohd Ridwan Razali - Razali, Mohd Ridwan (Faculty of Business and Management, 2009)
Triways Logistics is one of forwarding company that provides a service of forwarding by air, sea and land. It mission to be a world class total logistics services provider and become a pioneer in forwarding services. Outsourcing in other words can be best describing as third party logistics in logistics terms. The research study is to find the right outsourcing partnership by compare a company practices with the theory. This case study is exploring the gap of selecting a third party logistics that implement by Triways Logistics and the theories. In order to justify on what are the process that implement in outsourcing, the observation research has done for four months. From the observation, it was found that some issues related and influenced a process of choose an outsourcing partner. All these issues deeply explained in the report in order to be more clarifying for understanding of outsourcing or third party logistics (3PL). Some of suggestions have been explained in enhancing the service quality provided. Data collected through interview with the staff, supervisor and all departments related with the research studies.